Studies on the biology and ecology of the warthog 'Phacochoerus Aethiopicus Sundevalli' Lonnberg, 1908 in Zululand - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 1982.